(untitled) (Journal of Parents and Teachers, 2026)
Collaboration between teachers, management, parents and students leads to school discipline. This article recommends: teaching rules, enforcing discipline, using preventive strategies, encouraging everyone to participate and supporting teachers from the school management. Good discipline management creates a positive environment and promotes the comprehensive development of students.